Affect labeling: a promising new neuroscience-based approach to treating combat-related PTSD in veterans - Burklund, Lisa J.; Davies, Carolyn D.; Niles, Andrea; Torre, Jared B.; Brown, Lily; Vinograd, Meghan; Lieberman, Matthew D.; Craske, Michelle G. (Frontiers in Psychology, 2024)
Introduction A significant portion of individuals exposed to combat-related trauma will develop posttraumatic stress disorder (PTSD), a severe, debilitating disorder with adverse impacts on both mental and physical functioning. Current treatments are effective for many individuals, however, there is a need for new treatment approaches to improve outcomes in PTSD and address the many existing barriers to seeking or completing treatment. Methods In this open trial pilot study, we tested a novel, brief, computer-based intervention for PTSD utilizing “affect labeling” that was inspired by recent advances in neuroscience with U.S. veterans. Results As expected, pre-intervention clinical and fMRI neuroimaging data indicated that U.S. veterans with combat-related PTSD (N = 20) had significantly higher PTSD symptoms, depression symptoms, and amygdala reactivity to trauma cues than trauma-exposed healthy control veterans (N = 20). Veterans with PTSD who completed the affect labeling intervention (N = 13) evidenced reduced PTSD symptoms and these reductions were correlated with reductions in amygdala reactivity. Discussion Results from this initial proof-of-concept study are intriguing and suggest that affect labeling training offers significant potential as a novel, cost-effective, computer-based intervention for PTSD. Implications and next steps for further developing affect labeling interventions for PTSD are discussed. Clinical Trial Registration https://clinicaltrials.gov/, identifier NCT05924399.